Farmers' Motivation in Cultivating Patchouli Plants in Bencah Village Airgegas District South Bangka Regency - Indah Syawwalia; Evahelda Evahelda; Iwan Setiawan (Universitas Muhammadiyah Palembang, 2026)
Patchouli is an essential oil-producing crop that commands a high price and serves as a key Indonesian export commodity, contributing significantly to national foreign exchange earnings. While patchouli is cultivated in various regions across Indonesia—such as Aceh, Sumatra, Java, and Sulawesi—it is now also being developed in the Bangka Belitung Islands, specifically in Bencah Village, Airgegas District. This study aims to identify the motivations behind farmers' engagement in patchouli cultivation and to analyze the income of patchouli farmers in Bencah Village, Airgegas District, South Bangka Regency. A case study approach was employed, utilizing a census sampling method. Data were collected through observation, interviews, and questionnaires, and subsequently analyzed using both qualitative and quantitative descriptive methods. The results indicate that the patchouli cultivation process comprises several stages: nursery preparation, planting, maintenance, and finally, harvesting and post-harvest activities. Farmers' motivations for cultivating patchouli in Bencah Village fall into two categories: intrinsic and extrinsic. Intrinsic motivation stems from the farmers' personal drive—primarily the desire to utilize spare time—whereas extrinsic motivation arises from external factors, with farmer groups and market prices being the primary drivers. Extrinsic motivation was found to exert a greater influence than intrinsic motivation. Income analysis revealed that the average annual income of patchouli farmers is Rp 14,426,113.